(untitled) (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the study of level of the preparation of the using of the informatics technology of the school-leavers on the physics and mathematics department of the highschool. The groups of the formation’s criteria o f the inform competence are selected by the future teachers of the mathematics.